Had An Effect Of Debt Equity Ratio, Return On Assets, Firm Size, Earnings Per Share, Cash Position And Total Asset Turnover on Dividend Payout Ratio in Manufacturing Companies - Harahap, Qori Nurul Hasanah; Toni, Nagian; Simorangkir, Enda Noviyanti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The purpose of this study is to examine the effect of DER, ROA, Firm Size, EPS, Cash Position and Total Asset Turnover using the t test and F test. This research uses descriptive quantitative. The number of manufacturing companies used as a population is 169 companies selected based on purposive sampling obtained a sample of 54 companies. The data analysis technique used is multiple linear regression analysis. The results of data analysis show that partially only DER has a significant negative impact on DPR. Simultaneously, six independent variables have a significant impact on DPR. The coefficient of determination test results show the Adjusted R Square number 0.108, which means that 10.8% of the variation of DPR of manufacturing companies can be explained by the independent variables used, the remaining 89.2% is caused by other factors such as Growth Opportunity, Ownership, Current Ratio and others.